Neuromandibular integration in humans and chimpanzees: Implications for dental and mandibular reduction in Homo. Issue 1 (8th May 2018) - Veneziano, Alessio; Meloro, Carlo; Irish, Joel D.; Stringer, Chris; Profico, Antonio; De Groote, Isabelle
Abstract: Objectives: Although the evolution of the hominin masticatory apparatus has been linked to diet and food processing, the physical connection between neurocranium and lower jaw suggests a role of encephalization in the trend of dental and mandibular reduction. Here, the hypothesis that tooth size and mandibular robusticity are influenced by morphological changes in the neurocranium was tested. Materials and Methods: Three‐dimensional landmarks, alveolar lengths, and mandibular robusticity data were recorded on a sample of chimpanzee and human skulls. The morphological integration between the neurocranium and the lower jaw was analyzed by means of Singular Warps Analysis. Redundancy Analysis was performed to understand if the pattern of neuromandibular integration affects tooth size and mandibular robusticity. Results: There is significant morphological covariation between neurocranium and lower jaw in both chimpanzees and humans. In humans, changes in the temporal fossa seem to produce alterations of the relative orientation of jaw parts, while the influence of similar neurocranial changes in chimpanzees are more localized. In both species, postcanine alveolar lengths and mandibular robusticity are associated with shape changes of the temporal fossa. Conclusions: The results of this study support the hypothesis that the neurocranium is able to affect the evolution and development of the lower jaw, although most likely through functional integration of mandible, teeth, and muscles within the masticatory apparatus. This study highlights the relative influence of structural constraints and adaptive factors in the evolution of the human skull.